Wednesday

April 23, 2014

April 23, 2014

Posted by **alainia** on Friday, October 29, 2010 at 7:25pm.

(3y^-4)^2

- math -
**PsyDAG**, Saturday, October 30, 2010 at 5:05am5^-1 = 1/5, therefore

(5^-1p^4)^-2 = (p^4/5)^-2 = (5/p^4)^2 = 25/p^8

(3y^-4) = (1/3y)^4, therefore

(3y^-4)^2 = (1/3y)^8

**Related Questions**

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...

math-calculus - 15+2y-y^2/3y^2-16y+5 (5-y)(3+y)/(3y-1)(y-5) i factor out a ...

math - how do I solve this problem 2x/2=(6-3y)/2? 2x/2=(6-3y)/2? I solved it for...

math - Need help. solve 5 - y/3 for y= -3, 25 - y = 7 3y + 8 = 3, 5 - 3y =7, y/3...

Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...

countiblis,math - How did you get: x = 2; y = -1 for Directions: Sove the system...

math - Rewrite the equation so that y is the fucntion of x: a. 1/7(49-7y)=5x-3y+...

college algebra - 3y^2+8=0 (3y+2)+(3y-2)=8+0 3y=-8 y=3/8 Radical and Rational ...

mATH, ALGEBRA - i need help solving the system by addition. 5x-7y=5 x+3y=1 this ...

calculus - considering that x is the independent variable in this equation: y + ...